Method for synthesizing and preparing carbon nitride nanoparticles by using corn straws
By using corn stalks to prepare carbon nitride nanoparticles, the problems of high raw material toxicity and poor pore structure in existing technologies have been solved, achieving low-cost, high-performance nanoparticle preparation and expanding its application in optoelectronic sensing and biomedicine.
Patent Information
- Application Number
- CN202510811587.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-18
- Publication Date
- 2025-11-21
AI Technical Summary
Existing carbon nitride synthesis raw materials are highly toxic, costly, and dependent on fossil resources. The resulting nanoparticles have poor pore structure, making it difficult to achieve mass production and commercial application.
Using corn stalks as raw material, carbon nitride nanoparticles are prepared by adjusting the carbon-nitrogen ratio with urea and heat-treating with sodium citrate, avoiding the use of strong acids and bases, and forming a porous structure with a high specific surface area.
The prepared carbon nitride nanoparticles have high specific surface area, porosity, good photocatalytic performance and biocompatibility, and can be widely used in fields such as optoelectronic sensing and bioimaging. Moreover, the fluorescence emission wavelength can be tunable.
Smart Images

Figure CN120987272A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of nanomaterials technology, and in particular relates to a method for synthesizing carbon nitride nanoparticles using corn stalks. Background Technology
[0002] Carbon nitride is a two-dimensional nanomaterial with graphene-like functions, possessing advantages such as environmental friendliness, high specific surface area and porosity, excellent photocatalytic performance, multifunctionality, and low cost. Therefore, it has wide applications in photoelectric sensing, bioimaging, biomedicine, photocatalysis, and environmental remediation. Furthermore, this material exhibits good biocompatibility and chemical stability. Because carbon nitride nanoparticles are metal-free and non-toxic, they are particularly beneficial for practical applications such as public health monitoring. They can be cleverly used to design biosensors to detect and monitor various substances, improving the efficiency of environmental monitoring.
[0003] Currently, the raw materials for carbon nitride synthesis mainly consist of toxic and carcinogenic substances such as melamine, dicyandiamide, and thiourea. Furthermore, these chemical raw materials are costly and dependent on fossil resources, which hinders the mass production and commercialization of carbon nitride using this method. In addition, the carbon nitride nanoparticles prepared by existing methods have poor pore structure and contain many impurities.
[0004] Heilongjiang Province, a major corn-producing province, produces approximately 91 million tons of corn stalks annually, a figure that is increasing year by year. Traditional methods of stalk disposal (burning) cause air pollution, hindering ecological protection and sustainable development. Corn stalks, rich in nitrogen, can serve as a nitrogen source for nitrogen-containing substances. Therefore, corn stalks, as an important biomass energy resource, can be used to efficiently and cost-effectively produce carbon nitride, effectively solving the environmental pollution problems caused by stalk burning and realizing the resource utilization of waste. This also paves new avenues for the mass production and commercialization of carbon nitride. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a method for synthesizing carbon nitride nanoparticles using corn stalks. This method leverages the green, simple, and low-cost advantages of corn stalks to prepare carbon nitride nanoparticles (g-CNNPs). These carbon nitride nanoparticles possess environmental friendliness, high specific surface area, porosity, excellent photocatalytic performance, and multifunctionality. They can achieve signal output through fluorescence emission, emitting bright blue fluorescence at an excitation wavelength of 332 nm, and the fluorescence emission wavelength can be adjusted within the range of 400 nm to 600 nm. Therefore, they have wide applications in photoelectric sensing, bioimaging, biomedicine, photocatalysis, and environmental remediation.
[0006] The purpose of this invention is to provide a method for synthesizing carbon nitride nanoparticles using corn stalks, comprising the following steps:
[0007] S1. Soak corn stalk powder in urea solution and dry it to obtain pretreated corn stalk powder;
[0008] S2. The pretreated corn stalk powder and sodium citrate described in S1 are subjected to heat treatment and purified to obtain the carbon nitride nanoparticles.
[0009] In one embodiment of the present invention, in S1, the concentration of the urea solution is 60 g / L-100 g / L; by adjusting the carbon-nitrogen ratio of corn stalks with urea, the graphitization of the product is promoted, so that the final product forms a porous structure and increases the specific surface area.
[0010] In one embodiment of the present invention, in S1, the soaking time is 20h-28h.
[0011] In one embodiment of the present invention, in S1, the drying temperature is 30°C-35°C.
[0012] In one embodiment of the present invention, in S2, the mass ratio of the pretreated corn stalk powder to sodium citrate is (1-2):5; sodium citrate, as a mild reducing agent and structure directing agent, can inhibit the aggregation of final product particles and form a more uniform complex.
[0013] In one embodiment of the present invention, in S2, the heat treatment is performed under vacuum conditions at 160°C-200°C for 45-90 minutes.
[0014] In one embodiment of the present invention, in S2, the purification step includes sonication, centrifugation, and filtration.
[0015] In one embodiment of the present invention, in S2, the power of the ultrasound is 95W-105W and the duration is 6h-10h.
[0016] In one embodiment of the present invention, in S2, the centrifugation speed is 1900rpm-2100rpm and the time is 4min-6min.
[0017] In one embodiment of the present invention, in S2, the filter membrane used for filtration is a 0.22 μm filter membrane.
[0018] The technical solution of the present invention has the following advantages compared with the prior art:
[0019] (1) The method described in this invention adjusts the carbon-nitrogen ratio of corn stalks with urea to promote graphitization, thereby enabling carbon nitride nanoparticles to form a porous structure and increase the specific surface area. Sodium citrate is used as a mild reducing agent and structure directing agent, which can inhibit the aggregation of carbon nitride nanoparticles and form a more uniform material.
[0020] (2) Compared with bulk carbon nitride, the carbon nitride nanoparticles prepared by the method described in this invention have the advantages of sustainability, high specific surface area, porosity, good photocatalytic performance, environmental friendliness, and multifunctionality. Firstly, the carbon nitride nanoparticles prepared by this invention have a high specific surface area (up to 389.2 m²). 2 / g), with a molecular particle size of less than 15nm, while bulk carbon nitride is typically only 10nm. 2 The high specific surface area ( / g) provides more catalytically active sites for the reaction. Furthermore, these carbon nitride nanoparticles exhibit quantum size effects, emitting bright blue fluorescence at a 332 nm excitation wavelength, with the fluorescence emission wavelength tunable within the 400 nm-600 nm range. Moreover, the nanostructure shortens the electron-hole pair migration path, resulting in a 15-fold increase in the photocatalytic water splitting hydrogen production rate compared to bulk carbon nitride. Finally, these carbon nitride nanoparticles possess high biocompatibility and can be used as fluorescent labeling or drug carriers.
[0021] (3) The method described in this invention uses solid-phase pyrolysis to synthesize the product, avoiding the use of strong acids and bases and reducing waste liquid pollution. Attached Figure Description
[0022] To make the content of this invention easier to understand, the invention will be further described in detail below with reference to specific embodiments and accompanying drawings, wherein:
[0023] Figure 1 This is a flowchart illustrating the synthesis and preparation of carbon nitride nanoparticles using corn stalks according to the present invention.
[0024] Figure 2 This is a TEM image of the carbon nitride nanoparticles prepared in Example 1 of the present invention;
[0025] Figure 3 This is a TEM image of the carbon nitride nanoparticles prepared in Comparative Example 3 of this invention.
[0026] Figure 4 The fluorescence spectrum of carbon nitride nanoparticles prepared in Example 1 of this invention;
[0027] Figure 5 The fluorescence spectrum of carbon nitride nanoparticles prepared in Comparative Example 1 of this invention is shown.
[0028] Figure 6 The fluorescence spectrum of carbon nitride nanoparticles prepared in Comparative Example 2 of this invention is shown. Detailed Implementation
[0029] As described in the background section, the synthesis of carbon nitride currently relies mainly on chemical raw materials such as melamine, dicyandiamide, and thiourea. However, these raw materials present several problems: firstly, they are toxic and may even be carcinogenic, posing potential hazards to the environment and human health; secondly, these raw materials are expensive and mainly derived from fossil resources, which not only increases production costs but also makes the synthesis process of carbon nitride highly dependent on resources, hindering sustainable development. Therefore, existing synthesis methods are insufficient for the mass production and commercial application of carbon nitride. Furthermore, carbon nitride nanoparticles prepared by existing methods also suffer from some quality issues. For example, their pore structure is not ideal, failing to meet the microstructure requirements of high-performance materials; simultaneously, the high impurity content in the product further limits the performance and application range of carbon nitride nanoparticles in practical applications.
[0030] To address the aforementioned technical problems, this invention provides a method for synthesizing carbon nitride nanoparticles using corn stalks. The carbon nitride nanoparticles (g-CNNPs) prepared using the green, simple, and low-cost advantages of corn stalks possess environmental friendliness, high specific surface area, porosity, excellent photocatalytic performance, and multifunctionality. They can achieve signal output through fluorescence emission, emitting bright blue fluorescence at an excitation wavelength of 332 nm, and their fluorescence emission wavelength can be adjusted within the range of 400 nm to 600 nm. Therefore, they show broad application prospects in photoelectric sensing, bioimaging, biomedicine, photocatalysis, and environmental remediation.
[0031] The purpose of this invention is to provide a method for synthesizing carbon nitride nanoparticles using corn stalks, comprising the following steps:
[0032] S1. Soak corn stalk powder in urea solution and dry it to obtain pretreated corn stalk powder;
[0033] S2. The pretreated corn stalk powder and sodium citrate described in S1 are subjected to heat treatment and purified to obtain the carbon nitride nanoparticles.
[0034] In one embodiment of the present invention, in S1, the concentration of the urea solution is 60 g / L-100 g / L, for example, it can be 60 g / L, 61 g / L, 62 g / L, 63 g / L, 64 g / L, 65 g / L, 66 g / L, 67 g / L, 68 g / L, 69 g / L, 70 g / L, 71 g / L, 72 g / L, 73 g / L, 74 g / L, 75 g / L, 76 g / L, 77 g / L, 78 g / L, 79 g / L, 80 g / L, etc. Urea can be used to adjust the carbon-nitrogen ratio of corn stalks, promoting graphitization of the product, forming a porous structure in the final product, and increasing the specific surface area.
[0035] In one embodiment of the present invention, in S1, the soaking time is 20h-28h, for example, it can be 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, etc.
[0036] In one embodiment of the present invention, in S1, the drying temperature is 30°C-35°C, for example, it can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, etc.
[0037] In one embodiment of the present invention, in S2, the mass ratio of the pretreated corn stalk powder to sodium citrate is (1-2):5, for example, it can be 1:5, 1.1:5, 1.2:5, 1.3:5, 1.4:5, 1.5:5, 1.6:5, 1.7:5, 1.8:5, 1.9:5, 2:5, etc.; sodium citrate, as a mild reducing agent and structure directing agent, can inhibit the aggregation of final product particles and form a more uniform complex.
[0038] In one embodiment of the present invention, in S2, the heat treatment is performed under vacuum conditions at 160°C-200°C for 45-90 minutes. The temperature can be, for example, 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C, 170°C, 171°C, 172°C, 173°C, or 174°C. Temperatures ranged from 175℃, 176℃, 177℃, 178℃, 179℃, 180℃, 181℃, 182℃, 183℃, 184℃, 185℃, 186℃, 187℃, 188℃, 189℃, 190℃, 191℃, 192℃, 193℃, 194℃, 195℃, 196℃, 197℃, 198℃, 199℃, to 200℃, with a time duration of 45 minutes. in, 46min, 47min, 48min, 49min, 50min, 51min, 52min, 53min, 54min, 55min, 56min, 57min, 58min, 59min, 60min, 61min, 62min, 63min, 64min, 65min, 66min, 67min, 68 min, 69min, 70min, 71min, 72min, 73min, 74min, 75min, 76min, 77min, 78min, 79min, 80min, 81min, 82min, 83min, 84min, 85min, 86min, 87min, 88min, 89min, 90min, etc.
[0039] In one embodiment of the present invention, in S2, the purification step includes sonication, centrifugation, and filtration.
[0040] In one embodiment of the present invention, in S2, the power of the ultrasound is 95W-105W, for example, it can be 95W, 96W, 97W, 98W, 99W, 100W, 101W, 102W, 103W, 104W, 105W, etc.; the duration is 6h-10h, for example, it can be 6h, 7h, 8h, 9h, 10h, etc.
[0041] In one embodiment of the present invention, in S2, the centrifugation speed is 1900rpm-2100rpm, for example, it can be 1900rpm, 1910rpm, 1920rpm, 1930rpm, 1940rpm, 1950rpm, 1960rpm, 1970rpm, 1980rpm, 1990rpm, 2000rpm, 2010rpm, 2020rpm, 2030rpm, 2040rpm, 2050rpm, 2060rpm, 2070rpm, 2080rpm, 2090rpm, 2100rpm, etc., and the time is 4min-6min, for example, it can be 4min, 5min, 6min, etc.
[0042] In one embodiment of the present invention, in S2, the filter membrane used for filtration is a 0.22 μm filter membrane.
[0043] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. It should be understood that the specific embodiments are only used to explain the present invention, but the embodiments are not intended to limit the present invention.
[0044] In this invention, unless otherwise stated, the technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0045] In this invention, unless otherwise stated, the term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0046] In this invention, unless otherwise specified, the experimental methods used in the embodiments of this invention are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.
[0047] Example 1
[0048] Reference Figure 1 As shown, the method for synthesizing carbon nitride nanoparticles using corn stalks in this embodiment specifically includes the following steps:
[0049] S1. Grind the dehulled corn stalks into powder using a 550W grinder, then soak them in an 80g / L urea solution for 24 hours. Finally, dry the stalk powder in an oven at 30°C to obtain pretreated corn stalk powder.
[0050] S2. Weigh the pretreated corn stalk powder and sodium citrate in a mass ratio of 1.5:5 into a mortar and grind them into powder. Place the mixed powder into a crucible and keep it in a vacuum drying oven at 180°C for 60 minutes. The resulting brownish-yellow powder is carbon nitride nanoparticles (g-CNNPs).
[0051] S3. Dissolve the brownish-yellow powder in 1×TBS solution and sonicate for 8 hours. Then centrifuge at 2000 rpm for 5 minutes. Filter the supernatant through a 0.22 μm filter membrane to remove straw fibers. After drying, carbon nitride nanoparticles (g-CNNPs, specific surface area approximately 389.2 m²) are obtained. 2 Store in a refrigerator at 4°C for later use (g).
[0052] Example 2
[0053] Reference Figure 1 As shown, the method for synthesizing carbon nitride nanoparticles using corn stalks in this embodiment specifically includes the following steps:
[0054] S1. Grind the dehulled corn stalks into powder using a 550W grinder, then soak them in a 60g / L urea solution for 24 hours. Finally, dry the stalk powder in an oven at 30°C to obtain pretreated corn stalk powder.
[0055] S2. Weigh the pretreated corn stalk powder and sodium citrate in a mass ratio of 1.5:5 into a mortar and grind them into powder. Place the mixed powder into a crucible and keep it in a vacuum drying oven at 160℃ for 70 minutes to obtain a brownish-yellow powder.
[0056] S3. Dissolve the brownish-yellow powder in 1×TBS solution and sonicate for 8 hours. Then centrifuge at 2000 rpm for 5 minutes. Filter the supernatant through a 0.22 μm filter membrane to remove straw fibers. After drying, carbon nitride nanoparticles (g-CNNPs, specific surface area approximately 374.5 m²) are obtained. 2 Store in a refrigerator at 4°C for later use (g).
[0057] Example 3
[0058] Reference Figure 1 As shown, the method for synthesizing carbon nitride nanoparticles using corn stalks in this embodiment specifically includes the following steps:
[0059] S1. Grind the dehulled corn stalks into powder using a 550W grinder, then soak them in a 100g / L urea solution for 24 hours. Then dry the stalk powder in an oven at 30℃ to obtain pretreated corn stalk powder.
[0060] S2. Weigh the pretreated corn stalk powder and sodium citrate in a mass ratio of 1.5:5 into a mortar and grind them into powder. Place the mixed powder into a crucible and keep it in a vacuum drying oven at 200℃ for 45 minutes to obtain a brownish-yellow powder.
[0061] S3. Dissolve the brownish-yellow powder in 1×TBS solution and sonicate for 8 hours. Then centrifuge at 2000 rpm for 5 minutes. Filter the supernatant through a 0.22 μm filter membrane to remove straw fibers. After drying, carbon nitride nanoparticles (g-CNNPs, specific surface area approximately 387.3 m²) are obtained. 2 Store in a refrigerator at 4°C for later use (g).
[0062] Comparative Example 1
[0063] The process is basically the same as in Example 1, except that the concentration of the urea solution is replaced with 20 g / L. Specifically, the steps include:
[0064] S1. Grind the dehulled corn stalks into powder using a 550W grinder, then soak them in a 20g / L urea solution for 24 hours. Finally, dry the stalk powder in an oven at 30°C to obtain pretreated corn stalk powder.
[0065] S2. Weigh the pretreated corn stalk powder and sodium citrate in a mass ratio of 1.5:5 into a mortar and grind them into powder. Place the mixed powder into a crucible and keep it in a vacuum drying oven at 180°C for 60 minutes to obtain a brownish-yellow powder.
[0066] S3. Dissolve the brownish-yellow powder in 1×TBS solution and sonicate for 8 hours. Then centrifuge at 2000 rpm for 5 minutes. Filter the supernatant through a 0.22 μm filter membrane to remove straw fibers. Dry the supernatant to obtain carbon nitride nanoparticles (g-CNNPs) and store them in a 4℃ refrigerator for later use.
[0067] Comparative Example 2
[0068] The process is basically the same as in Example 1, except that the temperature of the vacuum drying oven is set to 100°C. Specifically, the process includes the following steps:
[0069] S1. Grind the dehulled corn stalks into powder using a 550W grinder, then soak them in an 80g / L urea solution for 24 hours. Finally, dry the stalk powder in an oven at 30°C to obtain pretreated corn stalk powder.
[0070] S2. Weigh the pretreated corn stalk powder and sodium citrate in a mass ratio of 1.5:5 into a mortar and grind them into powder. Place the mixed powder into a crucible and keep it in a vacuum drying oven at 100°C for 60 minutes to obtain a brownish-yellow powder.
[0071] S3. Dissolve the brownish-yellow powder in 1×TBS solution and sonicate for 8 hours. Then centrifuge at 2000 rpm for 5 minutes. Filter the supernatant through a 0.22 μm filter membrane to remove straw fibers. Dry the supernatant to obtain carbon nitride nanoparticles (g-CNNPs) and store them in a 4℃ refrigerator for later use.
[0072] Comparative Example 3
[0073] The process is basically the same as in Example 1, except that the mass ratio of pretreated corn stalk powder to sodium citrate is changed to 3:5. Specifically, the steps include:
[0074] S1. Grind the dehulled corn stalks into powder using a 550W grinder, then soak them in an 80g / L urea solution for 24 hours. Finally, dry the stalk powder in an oven at 30°C to obtain pretreated corn stalk powder.
[0075] S2. Weigh the pretreated corn stalk powder and sodium citrate in a mass ratio of 3:5 into a mortar and grind them into powder. Place the mixed powder into a crucible and keep it in a vacuum drying oven at 180°C for 60 minutes to obtain a brownish-yellow powder.
[0076] S3. Dissolve the brownish-yellow powder in 1×TBS solution and sonicate for 8 hours. Then centrifuge at 2000 rpm for 5 minutes. Filter the supernatant through a 0.22 μm filter membrane to remove straw fibers. After drying, carbon nitride nanoparticles (g-CNNPs) are obtained and stored in a refrigerator at 4°C for later use. The fluorescence value of the carbon nitride nanoparticles was tested and found to be much lower than that in Example 1.
[0077] Comparative Example 4
[0078] Bulk carbon nitride was synthesized by thermal polycondensation: melamine was directly heated to 520°C and held for 3 hours, and then ground to obtain bulk carbon nitride.
[0079] Although this method for synthesizing bulk carbon nitride is simple, the product has a low specific surface area (only 10 m²). 2 / g), and contains structural defects.
[0080] Test Example 1
[0081] The carbon nitride nanoparticles prepared in Example 1 and Comparative Example 3 were characterized by TEM, and the results are as follows: Figures 2-3 As shown. From Figure 2 It can be seen that the carbon nitride nanoparticles prepared in Example 1 have a smaller particle size (less than 15 nm) and a larger specific surface area, thus providing more active sites. Figure 3It can be seen that the carbon nitride nanoparticles prepared in Comparative Example 3 have a larger particle size. This is because the amount of sodium citrate used in Comparative Example 3 is relatively low, resulting in less gas produced during pyrolysis, which leads to fewer pores and a smaller specific surface area in the material.
[0082] Test Example 2
[0083] Fluorescence spectra of carbon nitride nanoparticles from Examples 1 and 1-2 were measured. The excitation wavelength was set to 332 nm, the slit width to 10 nm, and the voltage to 500 V. The results are shown in Table 1 and 2. Figures 4-6 As shown:
[0084] Table 1
[0085] Sample Example 1 Comparative Example 1 Comparative Example 2 Fluorescence intensity (au) 3506 2261 754.4
[0086] From Table 1 and Figure 4 It can be seen that the fluorescence value of the carbon nitride nanoparticles prepared in Example 1 reached 3506 a.u.; from Table 1 and Figure 5 It can be seen that the fluorescence value of the carbon nitride nanoparticles prepared in Comparative Example 1 is lower than that in Example 1. This is because the low urea concentration leads to a low nitrogen-to-carbon ratio in the corn stalks, resulting in insufficient nitridation of the product. (See Table 1 and...) Figure 6 It can be seen that the fluorescence value (754.4au) of the carbon nitride nanoparticles prepared in Comparative Example 2 is lower than that in Example 1. This is because the product is not fully carbonized or nitrided due to the low pyrolysis temperature, resulting in an incomplete structure.
[0087] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for synthesizing carbon nitride nanoparticles using corn stalks, characterized in that, Includes the following steps: S1. Soak corn stalk powder in urea solution and dry it to obtain pretreated corn stalk powder; S2. The pretreated corn stalk powder and sodium citrate described in S1 are subjected to heat treatment and purified to obtain the carbon nitride nanoparticles.
2. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 1, characterized in that, In S1, the concentration of the urea solution is 60 g / L to 100 g / L.
3. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 1, characterized in that, In S1, the soaking time is 20h-28h.
4. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 1, characterized in that, In S1, the drying temperature is 30℃-35℃.
5. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 1, characterized in that, In S2, the mass ratio of the pretreated corn stalk powder to sodium citrate is (1-2):
5.
6. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 1, characterized in that, In S2, the heat treatment is performed under vacuum conditions at 160°C-200°C for 45-90 minutes.
7. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 1, characterized in that, In S2, the purification steps include sonication, centrifugation, and filtration.
8. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 7, characterized in that, In S2, the power of the ultrasound is 95W-105W, and the duration is 6h-10h.
9. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 7, characterized in that, In S2, the centrifugation speed is 1900rpm-2100rpm and the time is 4min-6min.
10. The method for synthesizing carbon nitride nanoparticles using corn stalks according to claim 7, characterized in that, In S2, the filter used for filtration is a 0.22μm filter membrane.